The therapeutic use of yoga in occupational therapy for individuals with stroke - Andrews, Alexandra P., author; Schmid, Arlene A., advisor; Atler, Karen, committee member; Portz, Jennifer Dickman, committee member (Colorado State University. Libraries, 2018)
The purpose of this study was to provide a description of the experiences of occupational therapists (OT) who are currently using yoga in occupational therapy practice for individuals that have experienced a stroke. Specifically, this study aimed to understand how and why OTs may be integrating yoga into rehabilitation for stroke. Ten OTs from around the United States completed a survey and comprehensive interview. Interview data was analyzed using an iterative process and both deductive and inductive coding. Themes in the data emerged related to the perceived benefits of integrating yoga in occupational therapy for stroke including: how yoga promoted client-centered recovery; that yoga brought "context" to therapy; and how yoga could be used to address multiple physical, emotional, and psychosocial needs following stroke. Based on these findings, yoga is currently being integrated into health care and specifically into occupational therapy. Yoga may be a beneficial means of therapy for individuals post-stroke to aide in physical and psychosocial rehabilitation and increase reintegration into life after stroke. While this study highlights a sample of OTs using yoga in practice, these findings do not serve as a guideline for OTs, but rather describe why OTs have chosen to use this complementary approach.
Keywords: occupational therapy; yoga; stroke; CVA